2018
DOI: 10.5603/kp.a2017.0202
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment according to the SCORE risk chart — from history, through present, to the future

Abstract: Karolina Adamkiewicz, MBBS BA (Hons) is a recent graduate of the King's College London School of Medical Education. She has previously completed her pre-clinical studies and BA at St. John's College, University of Cambridge. Currently, she is undertaking her Foundation training at the Royal London Hospital in the United Kingdom and has a keen interest in assessing cardiovascular risk and cardio-oncology. Doctor Adamkiewicz is focused on early risk stratification and identification of high-risk patients in non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Risk stratification scores applicable for other patient populations, like euroSCORE for coronary heart disease patients, SCORE risk chart for the general cardiovascular risk stratification [8], or CHA 2 DS 2 -VASc score for atrial fibrillation patients, have been accepted as very useful. Similar prognostic evaluation of CRT patients would have obvious potential applications for the assessment of CRT indications, guiding further therapy, counselling, and other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Risk stratification scores applicable for other patient populations, like euroSCORE for coronary heart disease patients, SCORE risk chart for the general cardiovascular risk stratification [8], or CHA 2 DS 2 -VASc score for atrial fibrillation patients, have been accepted as very useful. Similar prognostic evaluation of CRT patients would have obvious potential applications for the assessment of CRT indications, guiding further therapy, counselling, and other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Li et al demonstrated a positive correlation between the estimated pulse wave velocity (ePWV) and all-cause mortality when the ePWV is greater than 6.7 m/s [12]. It is also important to note that a traditional 10 year Systematic Coronary Risk Evaluation (SCORE) scale may potentially underestimate cardiovascular risk in patients with diabetes, central obesity, low HDL, and elevated triglyceride levels [17,18]. For instance, the calculated SCORE risk scale for the presented case is 3.4% [19] which indicated a low risk of cardiovascular event.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were also asked if they find their work stressful and for their work schedule: regular working hours or shift work. All patients had their CV risk assessed using SCORE tables, verified for the national population [12,13].…”
Section: Methodsmentioning
confidence: 99%